Presentacion de resultados de investigación: Proyecto I+D 2015-2019 ‘España, Seguridad y fronteras exteriores europeas en el área del Estrecho’ (DER2015-68147-R) / Presentation of Research Results: R&D Project 2015-2019 "Spain, Security and European External Borders in the Strait of Gibraltar Area" (DER2015-68147-R) - Torrejón Rodríguez, Juan Domingo; Calvo Mariscal, Lorena (PEACE & SECURITY-PAIX ET SÉCURITÉ INTERNATIONALES (EuroMediterranean Journal of International Law and International Relations), 2020)
Presentacion de resultados de investigación: Proyecto I+D 2015-2019 ‘España, Seguridad y fronteras exteriores europeas en el área del Estrecho’ (DER2015-68147-R) – Español Presentation of Research Results: R&D Project 2015-2019 ‘Spain, Security And European External Borders In The Strait of Gibraltar Area’ (DER2015-68147-R) – English